Measuring corporate sustainability maturity : a case study of Valmet Automotive's personnel - Merikallio, Minna (2023)
The automotive industry is undergoing a transformation process towards a more environmentally friendly and sustainable future. Nowadays, businesses recognize the increasing importance of staying ahead of competition in terms of sustainable development. Furthermore, the personnel are expected to have a mature understanding of sustainability issues. This prompts the question of how one can assess the extent of sustainability maturity within a company.